From patient to payment : - Newby, Cynthia (McGraw Hill Higher Education, 2005)
This concise, practical text-workbook provides extensive real-world practice with the universal medical insurance claim form, the HCFA 1500. Includes flow charts, claims processing forms, and medical reports. Coding and billing content is based on industry practice and addresses electronic claims and a variety of compliance issues. The text provides a brief introduction to MediSoft Advanced Patient Billing Software.